Pedagogical conditions for developing students’ professional competence based on pedagogical facilitation - Sanjar Abdivaitovich Aralov (Science and Education, 2025)
This article analyzes the significance and opportunities of using a pedagogical facilitation approach in the formation of students’ professional competence. Facilitation is viewed as a pedagogical technology that ensures active student participation in the learning process, fosters independent thinking, and develops problem-solving skills. The research identifies the components of professional competence (such as professional knowledge, skills, communicative abilities, reflective culture, and others) as well as the pedagogical conditions influencing their development (motivational environment, interactive methods, collaborative learning activities, mentoring systems, etc.).